楼上再N+1证时有错误,正确的如下:用数学归纳法:当n=1时左边=1=右边假设n=N时成立,则n=N+1时:1*(N+1)+2*(N+1-1)+3*(N+1-2)+...+N*(1+1)+(N+1)*1=1*N+1 + 2*(N-1)+2 + 3*(N-2)+3+...+N*1+N + (N+1)=1*N+2*(N-1)+3...
1*N+2*(N-1)+3*(N-2)+...+N*1=1/6N(N+1)(N+2)
2个回答
相关问题
-
1、1*n+2(n-1)+3(n-2)+……+(n-2)*3+(n-1)*2+n*1的和,如何求得1/6n(n+1)(n
-
为什么1*1+2*2+3*3+……+n*n=1/6n(n+1)(2n+1)
-
用数学归纳法证明:1*n+2(n-1)+3(n-2)+…+(n-1)*2+n*1=(1/6)n(n+1)(n+2)
-
1*n+2*(n-1)+3*(n-2)+…+n*1=1/6n(n+1)(n+2)数学归纳法证明
-
求证:[1/n+1]+[1/n+2]+…+[1/3n]>[5/6](n≥2,n∈N*).
-
1+2+3+4+……+n=n(n+1)(2n+1)/6
-
证明:1+2+3+……+n=1/6n(n+1)(2n+1)
-
1\n(n+1)+1\(n+1)(n+2)+1\(n+2)(n+3)+1\(n+3)(n+4)
-
求和:1*n+2(n-1)+3(n-2)+……+(n-2)*3+(n-1)*2+n*1 答案是n*(n+1)*(n+2)
-
1/2-1/n+1<1/2^2+1/3^2+……+1/n^2<n-1/n(n=2,3,4,5,6.